2016
DOI: 10.1161/cir.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Assessing Cardiorespiratory Fitness in Clinical Practice: A Case for Fitness as a Clinical Vital Sign: A Scientific Statement From the American Heart Association

Abstract: ABSTRACT:Mounting evidence has firmly established that low levels of cardiorespiratory fitness (CRF) are associated with a high risk of cardiovascular disease, all-cause mortality, and mortality rates attributable to various cancers. A growing body of epidemiological and clinical evidence demonstrates not only that CRF is a potentially stronger predictor of mortality than established risk factors such as smoking, hypertension, high cholesterol, and type 2 diabetes mellitus, but that the addition of CRF to trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
1,821
2
58

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,757 publications
(1,929 citation statements)
references
References 295 publications
(357 reference statements)
48
1,821
2
58
Order By: Relevance
“…The impact of a 1-U higher fitness level on incident HF is somewhat higher than that generally reported for cardiovascular and all-cause mortality by our group 7,24 and others. 6,9,12 For example, in a meta-analysis including >100 000 subjects, Kodama et al 9 reported that each 1-MET increment in exercise capacity was associated with 13% and 15% reductions in all-cause and cardiovascular mortality, respectively. Regardless, these observations collectively There are several potential explanations for the lower HF incidence among fitter subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of a 1-U higher fitness level on incident HF is somewhat higher than that generally reported for cardiovascular and all-cause mortality by our group 7,24 and others. 6,9,12 For example, in a meta-analysis including >100 000 subjects, Kodama et al 9 reported that each 1-MET increment in exercise capacity was associated with 13% and 15% reductions in all-cause and cardiovascular mortality, respectively. Regardless, these observations collectively There are several potential explanations for the lower HF incidence among fitter subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Thus physical activity and/or exercise interventions that improve VȮ2max should be emphasised in public health guidelines (Bouchard et al, 2015;Ross et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiopulmonary exercise testing (CPET) is an important clinical tool to assess the functions of the pulmonary, circulatory, and musculoskeletal systems [1,2]. In pediatric cardiology, CPET has become a standard procedure for monitoring and diagnosing patients with cardiorespiratory diseases [3,4].…”
Section: Introductionmentioning
confidence: 99%